A Function of Language Analysis Through Language Features Showed by Stella Grant in the Five Feet Apart Movie (2019 - Haya, Aqilla Fadia; Wulandari, Dwi (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2024)
Movie is the combination of audio and visual language in a movie makes it acceptable to the audience. This study aims to examine the language function and features used by women in the movie based on Stella's utterances. The researcher used features of language mentioned by Jennifer Coates’ (2013) and Roman Jakobson's (1960) theory function of language. This study used a descriptive qualitative method employed purposive sampling to collect data from the Five Feet Apart (2019) movie and the Five Feet Apart movie script. The results revealed that the main female characters use all language features. Features that Stella uses such as minimal responses, hedges, tag questions, questions, commands and directives, swearing and taboo languages, and compliments. Additionally, Stella mostly used expressive functions. The research also shows the social factor that Stella mostly used is a topic factor. Thus, it can be concluded that as the main female character, Stella Grant wants to express her feelings to her speech partner through her utterances which is included in the features of language